Herbal medicine use behaviour in Australian adults who experience anxiety: a descriptive study. Issue 1 (December 2016) - McIntyre, Erica; Saliba, Anthony; Wiener, Karl; Sarris, Jerome
Abstract Background Anxiety disorders are the most prevalent mental health condition in Australia. In addition, there are many people who experience problematic anxiety symptoms who do not receive an anxiety disorder diagnosis but require treatment. As herbal medicine use is popular in Australia, and little is known about how adults experiencing anxiety are using these medicines, this study aimed to identify how Australian adults who experience anxiety are using herbal medicines. Methods An online cross-sectional descriptive study was conducted using purposive convenience sampling to recruit Australian adults who have experienced anxiety symptoms and have used herbal medicines (N = 400). Descriptive statistics, chi-square test of contingency, analysis of variance, and simple logistic regression was used to analyse the data. Results Eighty two percent of participants experienced anxiety symptoms in the previous 12 months, with 47 % reporting having previously been diagnosed with an anxiety disorder. In addition, 72.8 % had used herbal medicines specifically for anxiety symptoms in their lifetime, while 55.3 % had used prescribed pharmaceuticals, with 27.5 % having used herbal medicines concurrently with prescribed pharmaceuticals. The Internet and family and friends were the most frequently used sources of information about herbal medicines. Forty eight percent of participants did not disclose their herbal medicine use to their doctor. Conclusions Herbal medicines are being used by adults with anxiety and are commonly self-prescribed for anxiety symptoms. Health practitioners who are experts in herbal medicine prescribing are consulted infrequently. In addition, herbal medicine use is often not disclosed to health practitioners. These behaviours are concerning as people may not be receiving the most suitable treatments, and their use of herbal medicines may even be dangerous. It is critical we develop a better understanding of why people are using these medicines, and how we can develop improved health literacy to help with treatment decision making to ensure people receive optimal care.